2003
DOI: 10.1046/j.1365-294x.2003.01992.x
|View full text |Cite
|
Sign up to set email alerts
|

The hierarchical spatial distribution of chloroplast DNA polymorphism across the introduced range of Silene vulgaris

Abstract: Silene vulgaris was introduced into North America sometime prior to 1800. In order to document the population structure that has developed since that time, collections were made from 56 local populations distributed among 9 geographical regions in eastern North America. Individual plants were characterized for chloroplast DNA (cpDNA) haplotype by restriction fragment size analysis of four noncoding regions of cpDNA amplified by polymerase chain reaction. A total of 19 cpDNA haplotypes were detected using this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
50
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 40 publications
12
50
1
1
Order By: Relevance
“…A similar finding has been reported in North America for the invasive plant Silene vulgaris (McCauley, Smith, Lisenbay, & Hsieh, 2003). In this case, S. vulgaris had undergone several colonization events associated with a demographic expansion process occurring after its introduction from Europe (McCauley et al, 2003). On the other hand, spatial genetic structure is expected to be stronger for maternally inherited genes (mitochondrial and chloroplast), which are dispersed through seed flow, than for nuclear genes which are dispersed by both pollen and seed flow (Ennos, 2001); in the present study only nuclear markers (AFLP) were used.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A similar finding has been reported in North America for the invasive plant Silene vulgaris (McCauley, Smith, Lisenbay, & Hsieh, 2003). In this case, S. vulgaris had undergone several colonization events associated with a demographic expansion process occurring after its introduction from Europe (McCauley et al, 2003). On the other hand, spatial genetic structure is expected to be stronger for maternally inherited genes (mitochondrial and chloroplast), which are dispersed through seed flow, than for nuclear genes which are dispersed by both pollen and seed flow (Ennos, 2001); in the present study only nuclear markers (AFLP) were used.…”
Section: Discussionsupporting
confidence: 88%
“…In R. nudiflora, low similarity across distances (IBD) indicates that species expansion has been a slow diffuse spread leading to a patchy environment (Lee, & Mitchell-Olds, 2011;Leiss, & Müller-Schäer, 2001) that is the result of multiple invasions and colonization/extinction events in the Yucatán Peninsula. A similar finding has been reported in North America for the invasive plant Silene vulgaris (McCauley, Smith, Lisenbay, & Hsieh, 2003). In this case, S. vulgaris had undergone several colonization events associated with a demographic expansion process occurring after its introduction from Europe (McCauley et al, 2003).…”
Section: Discussionsupporting
confidence: 86%
“…Although S. vulgaris exhibits population structure at an ecological timescale (McCauley 1998;Olson and McCauley 2002), populations in the United States and Europe have been isolated for only a few hundred years (McCauley et al 2003) and are found in disturbed areas that are not conducive to long-term population persistence. The lack of allopatric isolation and the presence of diverged haplotypes in similar geographic locations (Figure 1, Table 1) suggest that recent divergence in allopatry was not likely to generate the observed patterns of diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Garcke (Caryophyllaceae) seeds were collected from four regions (Virginia and New York/Vermont; central Europe, Czech Republic/Germany; and Siberia, Russia; Figure 1) and grown in the Institute of Arctic Biology greenhouse at the University of Alaska (Fairbanks, AK). Eight populations were located in Giles and Craig counties, Virginia (628, GR, CO, AJ, MV, AR, WR, and EB, Figure 1; listed as populations 3, 4, 5, 6, 11, 12, 14, and 15, respectively, in Olson and McCauley 2002), and four populations were located in New York (NY) and Vermont (Vt) (Vt17b, Vt100, and VtLnG, Figure 1; McCauley et al 2003). Of the central European populations, three were located near Prague, Czech Republic (Kovary Meadow, KM; Institute Garden, InG; Sedlac railway station, SD), two were in northern Moravia, Czech Republic (Mount Keprnik, MK4; Rychleby Mountains, RM), two were from southern Moravia (Klentnice, KL; Lednice, Ld), and the eighth population was located near Gemsteltal (GM) in the Allgauer Alps, Austria (Figure 1; Štorchová and Olson 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Comparable phylogeographical studies in other taxa using (mostly) maternally inherited molecular markers have uncovered examples of both repeated colonization events with essentially no or little reduction in genetic diversity (e.g. Stepien et al 2002;Facon et al 2003;McCauley et al 2003;Kolbe et al 2004), and instances of much reduced genetic diversity as a result of invasion bottlenecks (e.g. Tsutsui et al 2000;Downie 2002;Lee 2002).…”
Section: Inferences From Patterns Of Diversitymentioning
confidence: 99%